Education and training needs assessment of Diocesan archives and records management personnel - De la Paz, Lea M. (2001)
Record-keeping in the Roman Catholic Church in the Philippines dates back hundreds of years to the Spanish period. A sizable number of the permanent records created during that period still exist in diocesan curiae and parishes. These are considered by the Church as its archival heritage. The physical preservation of the documents, the information these contain and the dissemination of their use is left to the hands of the present-day diocesan personnel, namely: the chancellors, parish priests and lay ecclesiastical personnel. A similarly important task is the management of records. Since records-keeping and the administration of archives are only part of the responsibilities of the chancellors, parish priests and lay ecclesiastical personnel, this research was carried out in order to determine whether they have received training for the job, in which areas they should still receive training on and whether current education and training programs are able to answer their education and training needs.